STRATEGI PEMBERDAYAAN UNTUK MENGIKIS DISKRIMINASI TERHADAP KAUM PEREMPUAN - Abd. Rohman; Sugeng Rusmiwari; Ade Hermawan (REFORMASI, 2022)
The issue of violence and discrimination against women is still an international issue, even including the Sustainable Development Goals (SDGs) agenda. Discrimination against women occurs most often is violence, stereotypes and subordination of women. The purpose of this study was to reveal the efforts of local governments in empowering women to eradicate violence and discrimination against women. This study used a qualitative method with a descriptive approach. Determination of informants used purposive sampling technique and data analysis using Miles, Huberman, and Saldana models, namely data reduction, data presentation, data condensation, and drawing conclusions/verification. The research findings that the women's empowerment strategy carried out by the P3AP2KB Office of the Malang City Government are (1) strengthening political will by issuing policies for the protection and empowerment of women, as well as efforts to understand and strengthen regulations on the protection and empowerment of women. (2) encourage and strengthen the participation of women in various development programs of the Malang City Government, such as outreach activities, training, musrenbang, and the development of women's organizations. (3) provide guidance to women's limitations with a group approach and urge women to organize themselves both within women's circles and in partnership with men. These efforts are made so that women can empower their potential to contribute their interests and talents to create an independent and prosperous life. Women will also be more confident and be able to have the courage to speak out in public to express their opinions.AbstrakIsu kekerasan dan diskriminasi terhadap perempuan masih menjadi isu internasional, bahkan termasuk agenda Sustainable Development Goals (SDGs). Diskriminasi terhadap perempuan terjadi paling sering adalah kekerasan, stereotip dan subordinasi. Tujuan penelitian ini adalah mengungkapkan upaya Pemerintah Daerah dalam memberdayakan perempuan guna mengikis kekerasan dan diskriminasi terhadap perempuan. Penelitian menggunakan metode kualitatif dengan pendekatan deskriptif. Penentuan informan menggunakan teknik purposive sampling dan analisis data menggunakan model interaktif, yakni reduksi data, penyajian, kondensasi, dan penarikan simpulan/verifikasinya. Temuan penelitian bahwa strategi pemberdayaan perempuan yang dilakukan Dinas P3AP2KB Pemerintah Kota Malang adalah (1) penguatan political will dengan menerbitkan kebijakan perlindungan dan pemberdayaan perempuan, serta upaya pemahaman dan penguatan peraturan-peraturan tentang perlindungan dan pemberdayaan perempuan. (2) mendorong dan menguatkan keikutsertaan perempuan dalam  berbagai program pembangunan Pemerintah Kota Malang, seperti kegiatan sosialisasi, pelatihan, musrenbang, dan pengembangan organisasi perempuan. (3) melakukan pembinaan terhadap keterbatasan kaum perempuan dengan pendekatan kelompok-kelompok serta menghimbau kaum perempuan menghimpun diri baik dalam kalangan Perempuan saja maupun bermitra dengan laki-laki. Upaya tersebut dilakukan agar kaum perempuan dapat memberdayakan potensi yang di miliki untuk menyumbangkan minat dan bakatnya mewujudkan kehidupan diri yang mandiri dan sejahtera. Kaum perempuan juga akan lebih percaya diri dan dapat memberanikan dirinya untuk bersuara di depan publik menyampaikan pendapatnya.